Hybrid NMPC Applied to a Solar-powered Membrane Distillation System. Issue 1 (2019) - Gil, Juan D.; Mendes, Paulo R.C.; Andrade, G.A.; Roca, Lidia; Normey-Rico, Julio E.; Berenguel, Manuel
Abstract: This work proposes a hybrid control strategy for the optimal operation of a solar membrane distillation facility This kind of plants presents a hybrid nature allowing their operation in several modes, which must be properly selected according to the operating conditions. Thus, the control algorithm is based on a mixed logical dynamical characterization of the solar membrane distillation facility, combined with the application of a practical nonlinear model predictive control strategy for calculating the optimal control actions. The main objectives of the control system are to increase the operating temperature and the distillate production of the membrane distillation module, as well as the number of operational hours. For these goals, the control algorithm has to select the most appropriate operating mode and the optimal operating points in terms of water flow rate at each sampling time. Simulation results are presented for evidencing the benefits of the proposed control approach.